2016
DOI: 10.1117/12.2231182
|View full text |Cite
|
Sign up to set email alerts
|

Towards freeform curved blazed gratings using diamond machining

Abstract: Towards freeform curved blazed gratings using diamond machining.', in Advances in optical and mechanical technologies for telescopes and instrumentation II. Bellingham, Washington: SPIE, p. 99123. Proceedings of SPIE. (9912).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…They are increasingly used in pioneering optical designs offering abundant new opportunities for optical designers. 2 In particular, freeform surfaces help to improve compactness, image sharpness and contrast in a larger field of view. Freeform optics are therefore promising components for airborne or space-based hyperspectral imagers for their ability to reduce the overall dimension, and therefore mass, of the satellite's payload, which is a critical parameter in space imaging systems.…”
Section: The Astronomical Applications Of Freeform Opticsmentioning
confidence: 99%
“…They are increasingly used in pioneering optical designs offering abundant new opportunities for optical designers. 2 In particular, freeform surfaces help to improve compactness, image sharpness and contrast in a larger field of view. Freeform optics are therefore promising components for airborne or space-based hyperspectral imagers for their ability to reduce the overall dimension, and therefore mass, of the satellite's payload, which is a critical parameter in space imaging systems.…”
Section: The Astronomical Applications Of Freeform Opticsmentioning
confidence: 99%
“…The design uses a custom freeform blazed grating made on a five-axis ultra-precision diamond machine to get the best optical performance while keeping the size and weight as small as possible. Bourgenot C et al [ 67 ] from Durham University in the UK wrote about the technical challenges and progress made in making convex blazed gratings on an ultra-precision five-axis Moore machine. They also talked about how the gratings are used as optical pupil reflectors in an integrated grating imaging spectrometer (IGIS) integral field unit prototype.…”
Section: Fabrication Capability Of Convex Blazed Gratingsmentioning
confidence: 99%
“…Graham C et al [ 16 ] designed an all-aluminum, rugged, lightweight, free-form grating-based near-infrared hyperspectral moisture sensing imager, FYMOS, which was machined on a five-axis ultra-precision diamond machine. Bourgenot C et al [ 17 ] from Durham University, UK, reported the technical challenges and progress in preparing such curved blazed gratings on an ultra-precision five-axis Moore machine, describing their application in an integrated grating imaging spectrometer (IGIS) integral field unit prototype, in which the free-form gratings were used as optical pupil reflectors. Bourgenot C et al [ 18 ] also discussed new opportunities for free-form gratings machined with diamond, and identified NiP as the substrate providing the best roughness and profile quality in a comparison of free-form gratings machined with RSA aluminum 6061 and RSA aluminum 443 surfaces chemically coated with NiP with an average roughness of 2.5 nm RMS per blazed surface.…”
Section: Introductionmentioning
confidence: 99%